Pesticide, veterinary and other residues in food - Watson, D. H. 1952- (CRC Press ; Woodhead Pub., 2004)
This wide-ranging text reviews the wealth of recent research on assessing and managing the risks from pesticide, veterinary and other chemical residues in food. After an introductory chapter on the key issues in food toxicology, Part one covers the assessment and management of risks, with individual chapters on genetic susceptibility to dietary carcinogens, good agricultural practice and HACCP systems, targeted and rapid methods for analysing residues in food and ways of assessing the mutagenicity of chemicals in food. Part two looks at veterinary residues, covering their safety, toxicology and detection. Part three examines pesticides, with chapters on surveillance and detection methods for fungicides and herbicides. In the final part, there are chapters summarising a wide range of other chemical residues in food, from xenostrogens/endocrine disruptors and dietary estrogens to polycyclic aromatic hydrocarbons, dioxins and polychlorinated biphenyls. Pesticide, veterinary and other residues in food is a standard reference for all those concerned with ensuring the safety of food. Reviews residue detection, risk assessment and risk managementExtensive coverage of chemical residuesIndispensable resource for all food producers.
Keywords: Food -- Toxicology.; Food contamination.; Feed additive residues.; Veterinary drug residues.; Pesticide residues in food.; Nutritionally induced diseases.; Pesticides -- Environmental aspects.; Animals; elektronické knihy; electronic books